Facile and controllable surface-functionalization of TiO2 nanotubes array for highly-efficient photoelectrochemical water-oxidation - Kim, Jin Un; Han, Hyun Soo; Park, Joonsuk; Park, Woosung; Baek, Ji Hyun; Lee, Jae Myeong; Jung, Hyun Suk; Cho, In Sun (Journal of Catalysis, 2018)
We report facile and effective surface-functionalization of TiO2 nanotubes array (NTs) via a TiCl3-mediated solution treatment and its effects on the charge transport and transfer properties for photoelectrochemical (PEC) water-oxidation. TiO2 NTs with ∼5 μm length were prepared by hydrothermal-etching a TiO2 nanorods array. Subsequently, TiO2 NTs were treated with an aqueous TiCl3 solution at 80 °C to generate surface oxygen vacancies and to deposit a TiO2 nano-branch layer on the side-walls of TiO2 NTs, and these modifications were confirmed by X-ray photoelectron spectroscopy and transmission electron microscopy. Through electrochemical impedance spectroscopy analysis, we found that the TiCl3-mediated surface-functionalization of TiO2 NTs significantly improves the charge carrier transport and transfer properties, owing to the increase in the charge carrier density (due to the generation of surface oxygen vacancies) and surface roughness (due to the formation of nano-branches), respectively. The TiCl3 treatment considerably improves the incident photon-to-current conversion efficiency (IPCE) and photocurrent density of TiO2 NTs (especially at low-bias potentials) during the PEC water-oxidation, and the treated material demonstrates a maximum IPCE of ∼93% and a photocurrent density of ∼2.25 mA/cm2 at 1.23 V versus the reversible hydrogen electrode.
Keywords: Incident photon-to-current conversion efficiencies; Nano-branch; Photoelectrochemical water oxidation; Photoelectrochemical water splitting; Reversible hydrogen electrodes; Surface Functionalization; Surface oxygen vacancies; TiO2 nanotubes; Charge transport/transfer properties; Nano-branch; Oxygen vacancy; Photoelectrochemical water-splitting; Surface-functionalization; TiO2 nanotubes